2014
DOI: 10.1021/es404185m
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characterization and Source Apportionment of Household Fine Particulate Matter in Rural, Peri-urban, and Urban West Africa

Abstract: Household air pollution in sub-Saharan Africa and other developing regions is an important cause of disease burden. Little is known about the chemical composition and sources of household air pollution in subSaharan Africa, and how they differ between rural and urban homes. We analyzed the chemical composition and sources of fine particles (PM 2.5 ) in household cooking areas of multiple neighborhoods in Accra, Ghana, and in peri-urban (Banjul) and rural (Basse) areas in The Gambia. In Accra, biomass burning a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 39 publications
0
40
0
2
Order By: Relevance
“…In addition, aquatic species are often consumed and form a large part of the diet of rural populations in Africa. Thus, tissue residues in the flesh contribute to the daily intake of contaminants by humans [21] and also represent serious health consequences for biota [22]. In the present study, the biotransformation and oxidative stress responses in relation to chemical burden in the liver of male and female Nile crocodiles was investigated, with varying degrees of anthropogenic chemical contamination.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, aquatic species are often consumed and form a large part of the diet of rural populations in Africa. Thus, tissue residues in the flesh contribute to the daily intake of contaminants by humans [21] and also represent serious health consequences for biota [22]. In the present study, the biotransformation and oxidative stress responses in relation to chemical burden in the liver of male and female Nile crocodiles was investigated, with varying degrees of anthropogenic chemical contamination.…”
Section: Discussionmentioning
confidence: 99%
“…This leads to poor waste management practices which severely compromises air quality in these areas. Studies conducted in Accra, Ghana reported that, majority of households in the city manage their solid waste by openly burning the garbage (Boadi and Kuitunen, 2005;Amegah et al, 2012;Zhou et al, 2014). The combustion activities releases dioxins, furans and other air pollutants which severely impacts household and local air quality.…”
Section: Ensuring Sound Waste Management Practicesmentioning
confidence: 99%
“…Solid-waste burning was also a significant contributor to pollution in poor neighborhoods in Ghana, but not more wealthy neighborhood. 61 South Asia has some of the highest ambient particulate matter levels worldwide and increasingly many African cities have levels higher than high-income cities. 62 Long-term exposure to lead is associated with high blood pressure and clinical CVD.…”
Section: Environmental Infectious and Early Life Nutritional Risk Fmentioning
confidence: 99%